2014
DOI: 10.1016/j.jpeds.2013.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Rapid Neurodevelopmental Assessment Tool for 5 to 9 Year-Old Children in Bangladesh

Abstract: The rapid neurodevelopmental assessment tool shows promise as a tool for use by a range of professionals for identifying NDIs in children of primary school age. Further refinement for identifying specific impairments is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…For the screening and detection of ASD specifically, we identified three tools, namely the Modified Checklist for Autism in Toddlers, Revised with Follow‐up (Robins et al, ), the PAAS, (Perera et al, , ) and the TIDOS (Oner et al, ). To identify children with, or at risk of DD, we selected seven tools for use in LMIC, namely: the Guide for Monitoring Child Development (GMCD; Ertem et al, ); Malawi Developmental Assessment Tool (MDAT; Gladstone et al, ); Rapid Neurodevelopmental Assessment Tool (RNDA; Khan et al, , , ); TQSI (Durkin et al, , , ; Thorburn et al, ); Caregiver‐Reported Early Development Index (CREDI; McCoy et al, ); INTERGROWTH‐21st Neurodevelopment Assessment (Fernandes et al, ), and the 12‐month screener (Biasini et al, ). The Engle Scale and Survey (Verdisco et al, ) and the East‐Asia Pacific Early Child Development Scales (EAP‐ECDS; Rao et al, ) have been identified as promising tools, although limited information in the peer‐reviewed literature is currently available.…”
Section: Resultsmentioning
confidence: 99%
“…For the screening and detection of ASD specifically, we identified three tools, namely the Modified Checklist for Autism in Toddlers, Revised with Follow‐up (Robins et al, ), the PAAS, (Perera et al, , ) and the TIDOS (Oner et al, ). To identify children with, or at risk of DD, we selected seven tools for use in LMIC, namely: the Guide for Monitoring Child Development (GMCD; Ertem et al, ); Malawi Developmental Assessment Tool (MDAT; Gladstone et al, ); Rapid Neurodevelopmental Assessment Tool (RNDA; Khan et al, , , ); TQSI (Durkin et al, , , ; Thorburn et al, ); Caregiver‐Reported Early Development Index (CREDI; McCoy et al, ); INTERGROWTH‐21st Neurodevelopment Assessment (Fernandes et al, ), and the 12‐month screener (Biasini et al, ). The Engle Scale and Survey (Verdisco et al, ) and the East‐Asia Pacific Early Child Development Scales (EAP‐ECDS; Rao et al, ) have been identified as promising tools, although limited information in the peer‐reviewed literature is currently available.…”
Section: Resultsmentioning
confidence: 99%
“…The high inter‐rater reliability between child care professionals is consistent with that found previously for the RNDA in 0–9 years old (Khan et al . , , ). This has important implications for human resource development in a country with sparse expertise in this field.…”
Section: Discussionmentioning
confidence: 99%
“…) and 5–9 years (Khan et al . ). The objective of this study was to validate a Rapid Neurodevelopmental Assessment (RNDA) tool for use with young adolescents aged 10–16 years by child health professionals to identify NDIs.…”
Section: Introductionmentioning
confidence: 97%
“…Evidence‐based practices related to each of the clinical services are outlined in Table S1. In the course of the 3‐month training period, Child Health Physicians and Developmental Therapists are provided a 2‐week, hands‐on training in applying the Rapid Neurodevelopmental Assessment, an assessment tool developed and validated by the Bangladesh Protibondhi Foundation in collaboration with DSH (Khan et al, ; Khan et al, ; Khan et al, ; Muslima et al, ) for neurodevelopmental assessment of children ages 0–16 years. This training provides a comprehensive overview of normal development, delays, and disorders and is especially useful for newly engaged professionals.…”
Section: Methodsmentioning
confidence: 99%